AR estimation from data with measurement error - Lopez, Jessa S.
Abstract (Measurement error can modify the structure of a data, and worse, distorts the distribution of the data generating process (Chester, 1991). We present three methods based on spline smoothing and bootstrap in estimating an autoregressive process with measurement error. Simulation studies show that the methods are capable of estimating the parameter of interest more than the usual estimation even when the data is measured with error).